2024
DOI: 10.3390/children11010086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pediatric Chronic Urticaria with Emphasis on Clinical and Laboratory Characteristics and Treatment Response to Omalizumab: A Real-Life Experience from a Tertiary Allergy Center

Aylin Kont Özhan,
Tuğba Arıkoğlu

Abstract: Pediatric data on the clinical and etiologic features, treatment response, and use of omalizumab for chronic urticaria (CU) are quite limited. The aim of this study was to evaluate the clinical and demographic characteristics, laboratory findings, and response to treatment of CU in children. Children with a diagnosis of CU between 2019 and 2023 were included in the study. Information on demographic characteristics, clinical features, laboratory tests, provocation tests for inducible urticaria, urticaria activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Along this line, the presence of functional autoantibodies in the serum of CSU patients that is revealed by a positive ASST test may indicate an autoimmune pathway of CU. Previous reports identified a positive ASST in 22-53% of patients with CSU [2,11,26]. Our results further minimized the pathogenetic role of autoimmunity in CSU, since we found that ASSTs were positive only in two children with CSU.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Along this line, the presence of functional autoantibodies in the serum of CSU patients that is revealed by a positive ASST test may indicate an autoimmune pathway of CU. Previous reports identified a positive ASST in 22-53% of patients with CSU [2,11,26]. Our results further minimized the pathogenetic role of autoimmunity in CSU, since we found that ASSTs were positive only in two children with CSU.…”
Section: Discussionsupporting
confidence: 74%
“…A further result of the study was about the response to the treatment. Most studies showed that the response rate of children with CU to licensed doses of second-generation H1-antistamines is higher compared to the adult population [26,[28][29][30][31]. On the other hand, Ozen B [23] found that only 37% of 141 children responded to standard anti-H1 treatment.…”
Section: Discussionmentioning
confidence: 99%